Perfectly matched discrete layers for three-dimensional nonlinear soil–structure interaction analysis. (March 2016) - Lee, Jin Ho; Kim, Jung Han; Kim, Jae Kwan
Highlights: Three-dimensional (3D) perfectly matched discrete layers (PMDLs) are developed. A procedure determining parameters of the PMDLs for a layered half-space is proposed. These PMDLs can be combined with the detailed finite-element model of a soil region. Green's functions calculated with this new method agree well with existing solutions. These PMDLs are applied to a nonlinear 3D soil–structure interaction analysis. Abstract: The dynamic behavior of structures established in flexible ground can be greatly influenced by soil–structure interaction. The challenge with regard to soil–structure interaction is to model the nonlinear behavior of soil in the vicinity of the foundation, including the boundary nonlinearity at the interface and the radiation of energy into infinity simultaneously. In this study, a three-dimensional time-domain formulation of perfectly matched discrete layers (PMDLs) is developed. It can be combined with a detailed finite-element model of the near-field region surrounding the foundation. The developed PMDL formulation can minimize the modeling region. A procedure to determine the parameters of the three-dimensional PMDLs to model a layered half-space effectively and accurately is proposed. Green's functions are calculated in half-spaces with the developed method and found to agree well with existing solutions. The developed PMDL formulation is applied to a nonlinear three-dimensional soil–structure interaction analysis, confirming its capability.